2018
DOI: 10.1021/acsami.8b03800
|View full text |Cite
|
Sign up to set email alerts
|

Calix[4]arene-Based Porous Organic Nanosheets

Abstract: Calixarenes are a common motif in supramolecular chemistry but have rarely been incorporated in structurally well-defined covalent 2D materials. Such a task is challenging, especially without a template, because of the nonplanar configuration and conformational flexibility of the calixarene ring. Here, we report the first-of-a-kind solvothermal synthesis of a calix[4]arene-based 2D polymer (CX4-NS) that is porous, covalent, and isolated as few-layer thick (3.52 nm) nanosheets. Experimental and theoretical char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 58 publications
(80 reference statements)
0
32
0
Order By: Relevance
“…The 200 wt% iodine uptake value of CPP2 is superior to those of polymers reported in the literature, and notable among these are nitrogen-rich triptycene-based materials (NTP, 180 wt%), 59 calix [4]arene-based 2D macromolecules (CX4-NS, 114 wt%), 60 porphyrin and pyrene-based conjugated microporous polymers (Por-Py-CMP, 130 wt%), 61 nitrogen-containing materials (NRPPs, 192 wt%), 57 JLUE covalent organic polymer (JLUE-COP-3, up to 90.29%), 62 conjugated microporous polymers with thiophene units (SCMPs, 222 wt%), 34 hierarchically porous adamantane-based macromolecules (202 wt%), 63 triazine-based covalent frameworks (TTPT, 177wt%), 64 fluorine-enriched polymers (FCMP-600@1-4, up to 141 wt%) 65 and many others. 66,67 The iodine adsorbed by CPP1-3 could be released by simple heating of these latter polymers in air at 125°C.…”
Section: Iodine Uptake Studiesmentioning
confidence: 80%
“…The 200 wt% iodine uptake value of CPP2 is superior to those of polymers reported in the literature, and notable among these are nitrogen-rich triptycene-based materials (NTP, 180 wt%), 59 calix [4]arene-based 2D macromolecules (CX4-NS, 114 wt%), 60 porphyrin and pyrene-based conjugated microporous polymers (Por-Py-CMP, 130 wt%), 61 nitrogen-containing materials (NRPPs, 192 wt%), 57 JLUE covalent organic polymer (JLUE-COP-3, up to 90.29%), 62 conjugated microporous polymers with thiophene units (SCMPs, 222 wt%), 34 hierarchically porous adamantane-based macromolecules (202 wt%), 63 triazine-based covalent frameworks (TTPT, 177wt%), 64 fluorine-enriched polymers (FCMP-600@1-4, up to 141 wt%) 65 and many others. 66,67 The iodine adsorbed by CPP1-3 could be released by simple heating of these latter polymers in air at 125°C.…”
Section: Iodine Uptake Studiesmentioning
confidence: 80%
“…These characterization data clearly suggested that, among the four CMPs, CMP‐4 was the best adsorbent for iodine vapor uptake with a large capacity of 208 wt %. This result is higher than those of many reported materials related to iodine uptake (Supporting Information, Table S6) [12d, 21b, d, 23a, b, 27, 28] …”
Section: Resultsmentioning
confidence: 54%
“…The iodine vapor capture of CMPs was investigated in ambient air. The experiments were implemented under ambient pressure and at 75 °C, which was based on the typical nuclear fuel reprocessing conditions [27] . In this case, 10 mg of each material was weighed and placed in pre‐weighed glass vessels (2 mL), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was easy to regenerate the material through washing with mild ethanol, and therefore it can be recycled with a very small loss of the efficiency. 25 As another study covalent organic polymers 7 and 8 were also examined by Skorjanc et al in terms of pollutant sponges. These polymers were produced using viologens 4, 5 and nitrocalix [4] arene 4 for iodine and toxic dyes capture.…”
Section: Iodine Capture By Calixarene-based Covalent Polymersmentioning
confidence: 99%